The Effects of Gum Cordia on the Physicochemical, Textural, Rheological, Microstructural, and Sensorial Properties of Apple Jelly - Mahsa Hasani; Sedigheh Yazdanpanah (Journal of Food Quality)
The aim of this research was to study the effects of gum cordia on the physicochemical, color, textural, rheological, microstructural, and sensorial properties of apple jelly. Apple jelly was prepared by replacement of 0, 25, 50, 75, and 100% of pectin with gum cordia. The results showed that gum cordia had a significant effect on the physicochemical properties (ash, protein, TPC, DE, and color) of apple jelly. The total phenol content of the sample significantly increased with the addition of gums. The rheological properties showed that a sample containing 75% gum cordia was similar to control and had the highest apparent viscosity, loss moduli (G″), storage moduli (G′), and complex viscosity. Also, the sensorial properties showed that a sample containing 75% gum cordia had a high score in texture, taste, appearance, and overall acceptability. The results suggested that gum cordia as a polymer can be successfully employed for the formulation of jelly for improving technofunctional properties of jelly.